DTI-ALPS index decreased in patients with Type 2 Diabetes Mellitus - Yu, Shuncheng; Jiang, Hongjun; Yu, Langxuan; Liu, Tieli; Yang, Chun; Cao, Jiajun; Song, Qingwei; Miao, Yanwei; Wang, Weiwei (Frontiers in Neuroscience, 2024)
Backgrounds Type 2 Diabetes Mellitus (T2DM) has become a significant global public health issue, characterized by a rising prevalence and associated deficits across multiple organ systems. Our study aims to utilize the DTI-ALPS technique to assess the change of ALPS index in T2DM patients, and to explore whether such changes are correlated with cognition level and diffusion parameters. Methods The study involved 41 patients with T2DM (mean age, 60.49 ± 8.88 years) and 27 healthy controls (mean age, 58.00 ± 7.63 years). All subjects underwent MRI examination, cognitive assessment, and laboratory tests. Tract-based spatial statistics (TBSS) was used to evaluate white matter changes. GLM was performed to check the DTI-ALPS index difference between T2DM and HC groups. Spearman correlation analysis and partial correlation analysis were used to analyze the correlation between the DTI-ALPS index and diffusion properties & cognitive scores. Results The results show that the ALPS index was lower in T2DM patients. MoCA score was significantly correlated with the ALPS index. Patients with T2DM had a significant increase in both mean diffusivity (MD) and radial diffusivity (RD) and decrease in fractional anisotropy (FA) compared to the HC group. Conclusion The results suggest that the ALPS index is decreased in T2DM patients and associates with cognitive level.